ASH DEPOSITION CHARACTERISTICS ON BIOMASS FUEL - MYADYSOYUNOV, BATYR (IRC, 2017)
Nowadays, biomass is considered to be one of the best alternatives for the replacement of the gas and oil product fuels. The types of biomass that were used for this project are rice husk, kenaf, wastewater effluent and palm oil mill effluent. The purpose of this report was to investigate how mineral content of rice husk ash, kenaf ash, wastewater effluent ash and palm oil effluent ash are related to ash problems like corrosion, slagging and deposit formation. Samples were prepared according to NREL standard procedure and their mineral content was studied by the use of Atomic Absorption Spectroscopy. After the samples were prepared their ash content percentage was calculated, based on the results important graphs were plotted. Samples were checked for 8 elements which are: Ca, Cd, Cr, Cu, Fe, Ni, Pb and Zn. Based on the results, the most suitable biomass samples for energy production were selected.